Question Number 137627 by rs4089 last updated on 04/Apr/21 | ||
![]() | ||
Answered by MrGaster last updated on 16/Feb/25 | ||
![]() | ||
$$ \\ $$$$\mathrm{Prove}:\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\right]=\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }+\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}\overset{\rightarrow} {{u}}}{{dt}} \\ $$$$\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\right]=\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }+\left(\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\right)^{\mathrm{2}} \\ $$$$\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} {u}}{{dt}^{\mathrm{2}} }\right]=\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right]\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}+\overset{\rightarrow} {{u}}\frac{{d}}{{dt}}\left[\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right] \\ $$$$\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right]=\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{3}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{3}} }+\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} } \\ $$$$\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right]=\left(\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{3}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{3}} }+\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right)\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}+\overset{\rightarrow} {{u}}\frac{{d}}{{dt}}\left[\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right] \\ $$$$\frac{{d}}{{dt}}\left[\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right]=\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }+\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{3}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{3}} } \\ $$$$=\overset{\rightarrow} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{3}} \overset{\rightarrow} {{u}}}{{dt}}+\left(\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\right)^{\mathrm{2}} =\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }+\overset{\rightarrow} {{u}}\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} } \\ $$$$\begin{matrix}{\frac{{d}}{{dt}}\left[\overset{\rightarrow} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right]=\left[\overset{\_} {{u}}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{3}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{3}} }\right]}\\{\frac{{d}}{{dt}}\left[{u}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{2}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{2}} }\right]=\left[{u}\frac{{d}\overset{\rightarrow} {{u}}}{{dt}}\:\frac{{d}^{\mathrm{3}} \overset{\rightarrow} {{u}}}{{dt}^{\mathrm{3}} }\right]}\end{matrix} \\ $$ | ||